ПСИХОЛОГИЯ ФАНИНИНГ ДОЛЗАРБ ВАЗИФАЛАРИДАН БИРИ - Турсунов, Л.С. (SCIENCE and SOCIETY, 2024)
In the article, the main attention is focused on one of the current tasks of the science of psychology, and special aspects of scientific psychology are emphasized.